Teknik Perencanaan Pendidikan Di Madrasah Aliyah Darul Ihsan - Rambe, Ali Akbar; Azmi, Fachruddin; Tanjung, Akbar; Kesuma, Euis Indah; Daulay, Isma Hayati; Harahap, Khoirul Saleh; Fauzi, Mhd Armawi (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
The implementation of Islamic education planning is one of the important efforts in developing the education system at Al IQRA's Private Madrasah Ibtidaiyah (MIS) on Jalan PLTU No. 3 Belawan Sicanang. Madrasah Ibtidaiyah Al Iqra' was founded on December 12, 1995 and has been around for about 28 years. The research method used in the Islamic Education Planning Implementation research (Principles, Objectives, Functions, Cycles, Models and Work as well as Planning Information) at MIS Al Iqra' Belawan is a qualitative research method with a descriptive approach. This research resulted that the implementation of Islamic education planning at MIS Al IQRA' Belawan has made a positive contribution in increasing the effectiveness and quality of Islamic education. However, there is still room for further development, such as increasing parental involvement, developing holistic Islamic-based assessments, and applying technology in Islamic learning. Keywords: Implementation, Planning, Islamic Education.